Application of activity-based costing and time-driven activity-based costing for kitchen cabinet - Intan Noralisya, Mohd Yusoff; Mohd Yazid, Abu; Sri Nur Areena, Mohd Zaini (Springer Nature Singapore Pte Ltd, 2024)
Kitchen cabinets started to have a big historical impact on Malaysia with the advent of freestanding cabinets in western and colonial furniture in the 19th century. The drawback with traditional costing methods is that they fail to offer enough information about elements that are crucial to customers, such quality and service. Activity-based costing (ABC) was created to address traditional costing's limitations in complex product environments. However, it is not universally accepted as it overlooks unused capacity for forecasting. This work compares ABC and time-driven activity-based costing (TDABC) to assess cost sustainability in kitchen cabinet manufacturing. Data from a Johor-based furniture manufacturer was collected. The work successfully compares both methodologies, considering various factors. It concludes that both have strengths based on industry needs, but proving TDABC’s efficiency is essential as it is simpler, cheaper, and more powerful than ABC. Nonetheless, neither ABC nor TDABC is well-suited for kitchen cabinets manufacturing. The process of building kitchen cabinets involves inherent complexity, such as variations in measurements, material availability, and design specifications. Based on the given factors, such as higher uncertainties, biases in assumptions and inaccurate data collection, it will draw limitations in obtaining accurate and reliable data for ABC and TDABC.